2020
DOI: 10.1007/s11469-020-00342-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the English Version of the Fear of COVID-19 Scale and Its Relationship with Behavior Change and Political Beliefs

Abstract: The COVID-19 pandemic has many individuals around the world fearing for their lives. The constant news coverage, rapid transmission, and relatively high mortality rate, make fearfulness a natural response. To assess the fear of COVID-19, the Fear of COVID-19 Scale (FCV-19S) was developed. The primary aim of the present study was to conduct the first psychometric assessment and validation of the English version of the FCV-19S. Two samples were collected in New Zealand. Sample 1 comprised 1624 participants of wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
140
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 25 publications
27
140
9
1
Order By: Relevance
“…Unlike Harper et al (2020), who reported a weak to moderate (β=.20) effect of fear of COVID-19 on pandemic-related health behavior change, our study found no associations between fear of COVID-19 and physical distancing and hand washing. Our result is also in contrast with another study where the authors reported weak correlations (rho=.20 and rho=.11) between fear of COVID-19 and adherence to 2-m physical distancing in two samples collected in New Zealand (Winter et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike Harper et al (2020), who reported a weak to moderate (β=.20) effect of fear of COVID-19 on pandemic-related health behavior change, our study found no associations between fear of COVID-19 and physical distancing and hand washing. Our result is also in contrast with another study where the authors reported weak correlations (rho=.20 and rho=.11) between fear of COVID-19 and adherence to 2-m physical distancing in two samples collected in New Zealand (Winter et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Given the known effectiveness of fear as a motivator for behavior change (Tannenbaum et al 2015) and the above-mentioned reports of associations between fear of COVID-19 and relevant health behaviors, our results may appear unexpected. However, it needs to be noted that the associations reported in the UK (Harper et al 2020) and New Zealand (Winter et al 2020) should still be considered relatively small, and the discrepancies between these reports and our ndings from Saudi Arabia must therefore not be exaggerated. Lack of predictive effects may well be related to the fact that frequency of physical distancing and hand washing was overall high in the present sample, resulting in a ceiling effect.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Overall Cronbach's alpha was 0.93, and Cronbach's alpha values when item deleted were either .91 or .92. (Winter et al 2020) and one of the studies reporting data from a Hebrew version (Bitan et al 2020) was related to low means and possible oor effects for items 3, 6, and 7. The pattern of item means of the Tamil version appeared to be most similar to that of the Bangla version (Sakib et al 2020) and also similar to that found for the English-language version used in a sample in India (Doshi et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Fear of COVID-19 could worsen mental health and well-being (e.g. among university students, see Gritsenko et al 2020) or it could motivate individuals to comply with the recommended health measures (Harper et al 2020;Winter et al 2020). Ahorsu et al (2020) recently developed the Fear of which measures the severity of fear of COVID-19.…”
Section: Introductionmentioning
confidence: 99%